Analysis of the structure and criteria in the elaboration of a sustainability index - Feil, Alexandre André; Schreiber, Dusan (Sustainability in Debate, 2017)
The sustainability of human-environmental systems currently represents the best choice for its continuity. Sustainability index can be used for possibly identifying the direction of sustainability, although regarded as complex and subjective. Therefore, this study aims to analyze the process of constructing a sustainability index, by identifying main definitions, structure and methods. The used methodology included qualitative research, with data collection from literature review and interpretation analysis. The results illustrate that the structure of a sustainability index is developed by identifying the aims and the human-environmental system, by the selection, normalization, ponderation and aggregation of indices, thus generating the index. We conclude that there is no single model for the process of elaborating sustainability index, so different processes can be used, differing in their quality of measurement of sustainability. Additionally, the choice for a process is related to the available information on the measured subsystem. In this context, it is recommended great attention, once the generated index could present unsatisfactory and unrealistic results.